Pengaruh Strategi Pemasaran dan Kualitas Layanan Terhadap Keputusan Nasabah Pada Bank Syariah - Tri Anggraeni; Achmad Fauzi; Delila Rambe; Winda Afrillia; Nyai Rika Ambarwati; Hamdy Febrian (Prisani Cendekia, 2022)
The process of tracking issues, identifying problems to concluding when a consumer decides to become a customer of a financial institution which is seen as a solution to the needs and desires of the consumer, is known as a customer decision. This article reviews the influence of customer decisions, namely: Marketing Strategy and Service Quality. The author of this article aims to develop hypotheses about the effect of variables on each other to be used in subsequent research. The results of this literature review article are 1) Marketing Strategy for Customer Decisions; and 2) Quality of Service to Customer Decisions